Identifying Information, Motivation & Behavioral Factors and Its’ Relation to Diabetes Self-Care: A Qualitative Study among People with T2DM - Amirudin, Nadia; Panting, Albeny Joslyn; Kassim, Rosnani; Mohamed Aimanan, Siti Nurhanim; Ithnain, Norbaidurah (International Journal of Nursing and Health Services (IJNHS), 2023)
Background: Self-care in diabetes management is not a one-size-fits-all approach. It requires individualization based on factors such as age, lifestyle, social support, and overall health. Objective: This study aimed to qualitatively explore psychosocial aspects such as information, motivation & behavioral factors concerning diabetes self-care among people with type 2 Diabetes Mellitus (T2DM). Method: Purposive sampling was used to select patients with Type 2 Diabetes Mellitus from government health facilities in Klang, Selangor. They participated in an In-Depth Interview (IDI) session, which included a semi-structured guide questionnaire. All data were analyzed thematically. Results: A total of 21 IDIs consisting of nine females and twelve males T2DM patients were conducted with an average age of 56 years. The qualitative analysis identified three major themes: Information, Motivation, and Behavior. Conclusions: It is crucial to understand individual needs, capabilities, and the factors that affect type 2 diabetes patients' capacity to perform these self-care behaviors. Recommendation: Psychosocial aspects should be embedded in diabetes care settings to delay or prevent the progression of complications associated with Diabetes